ACMEOLOGICAL TRAINING IN PROSPECTIVE HIGHER EDUCATION TEACHER TRAINING - Protsenko., О. (Continuing Professional Education: Theory and Practice, 2023)
The author defines the concept of «acmeological training» as a ground for successful self-development of a prospective higher education teacher. The article regards acmeological training as one of acmeological technologies which serves to reveal the inner capacity, develop abilities and skills aimed at reaching high-level personal and professional development as well as professionalism. The author proves that acmeological trainings represent a form of active self-study methods, therefore, considering self-education, self-study, self-preparation, self-training as components of its content structure. The paper highlights the functions of acmeological trainings, namely educational, communicative, academic, developing, stimulating. Deliberate personality change and dynamic nature of personal and professional skills are classified as essential features of acmeological trainings. The acmeological training for a prospective specialist is based on the following methodological principles: subjectivity, activity, potentiality and actuality, modeling, operational and technological, feedback. The principles of sincerity, trust and privacy, the principle of the actual present are likewise applied. The acmeological training involves psychological impact owing to the integration of group and individual work methods. In the article the basic requirements for the organization of the acmeological training for future higher education teachers are defined. The article suggests basic requirements for trainers how to conduct and organize the acmeological training (to create an enabling environment during the training; to develop strategies of future higher education teachers self-study; modeling self-study methods).